Bond characteristics of high strength concrete - Alavi-Fard, Mehdi, 1959- (1999)
Thesis (Ph.D.)--Memorial University of Newfoundland, 1999. Engineering and Applied Science Bibliography: p. 237-254 High strength concrete is used mostly in the construction of bridges, high rise buildings and marine structures. Bond strength between high strength concrete and rebar is an important factor in designing any reinforced concrete structures under various kinds of loadings. Therefore, this study is conducted to investigate the strength of bond between high strength concrete and reinforcement, to determine the internal distribution of stresses and strains along the rebar interface with high strength concrete. -- In the experimental phase of this research a total of 150 specimens made of high strength concrete were cast to investigate the bond strength under monotonic and cyclic loading. The influences of load history, confining reinforcement, rebar diameter, concrete strength, rebar spacing, rate of pull out, and deformation pattern were investigated experimentally for reinforcement bars of 25 mm and 35 mm diameter. The internal concrete strains close to the contact surface and also the steel rebar strains were measured. The test set up, load application, instrumentation and measurement, test procedure, and type of materials were designed to measure accurate strains and deformations. Several specimens with different rebar diameters and rib geometries were tested. The range of the tested concrete compressive strengths was between 75 MPa and 95 MPa. The rib geometries were examined for rebar with nominal diameter of 25 mm and 35 mm. -- The test results revealed that the maximum bond stress of high strength concrete is higher than the corresponding one for normal strength concrete. However, the behavior of high strength concrete is more noniinear-brittle and it must be considered in the bond model. The development of a new technique of strain measurement around the steel rebar was unique and it can be useful to identify the internal crack pattern and to predict possible failure modes. The area under the curve of the bond stress-slip curve can define the bond energy. The bond energy should be used to evaluate the bond behavior rather than the maximum bond stress. A new expression for calculating bond stress based on the cubic root of concrete strength is recommended and the results are compared with similar equations. Also, the influences of several parameters under cyclic loading condition are investigated. -- In the numerical investigation, an attempt has been made to consider the effect of tension stiffening in the material model. The concepts of bond energy, fracture energy, tension softening and biaxial failure envelope of high strength concrete were applied in the development of a material model for high strength reinforced concrete. The improved model is implemented in the UMAT subroutine for use with the ABAQUS finite element program. In addition, three dimensional rebar element was added to the program in order that the new model will be able to analyze reinforced high strength concrete structures. The model has been checked against several standard problems. Further, A new parametric study based on the effect of bond energy on the fracture energy was introduced. Based on sensitivity analysis, the results were applied to analysis of slabs with low, moderate and high steel ratio. The modified model can be used to analyze reinforced high strength concrete members